The role of Halal awareness and Halal certification in influencing Malaysian intention to purchase Halal food and non-food products in Johor / Khadijah Maulad Bahrol and Nor Fasihah Supangat - Maulad Bahrol, Khadijah; Supangat, Nor Fasihah (Faculty of Business and Management, 2014)
This research is implemented to study about purchase intention towards factors that influence Malaysian customer in Johor area to buy Halal product. The study aimed to identify the major factors that influent purchasing Halal product such as Halal awareness, Halal certification, product quality, marketing promotion and also brand. The study was done within the area in Johor. The study was conducted at Syarikat Air Johor Holdings SdnBhd which located at Johor Bahru and Batu Pahat and around those particular areas. The sample size for this study is 100 of the respondents who walking around the area. Data obtained using two methods which are primary and secondary data. Respondents been asked to answer the questionnaires that contain the factor of influencing purchase intention of Halal product in Johor. Data are analyzed using Reliability Test, Chart, and Frequency Table through SPSS program. The sampling technique that has been used in this study was non-probability sampling techniques which is convenience sampling. The result shows that Halal certification is the major factor of influencing customer to purchase Halal product compared to other factors.